\(\left(3X-2^2.3\right):8+2.5=13\)
giúp mình với nha
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`@` `\text {Ans}`
`\downarrow`
`3^3 * x^2 - 2^4 * x^2 = 8^2 * 5 - 4^2 * 3^2`
`=> x^2 . (3^3 - 2^4) = 2^6 . 5 - 2^4 . 3^2`
`=> x^2 . 11 = 2^4 . (2^2 . 5 - 3^2)`
`=> x^2 . 11 = 2^4 . 11`
`=> x^2 . 11 - 2^4 . 11 = 0`
`=> 11 . (x^2 - 16) = 0`
`=> x^2 - 16 = 0`
`=> x^2 = 16`
`=> x^2 = (+-4)^2`
`=> x = `\(\pm4\)
Vậy, `x \in`\(\left\{4;-4\right\}\)
_____
\(\left[\left(\dfrac{1}{2}\right)^2-\left(\dfrac{1}{3}\right)^3\right]x+3^2\cdot2^2=4^2\cdot3\)
`=>`\(\left(\dfrac{1}{4}-\dfrac{1}{27}\right)x+\left(3\cdot2\right)^2=48\)
`=>`\(\dfrac{23}{108}\cdot x+6^2=48\)
`=>`\(\dfrac{23}{108}x=48-6^2\)
`=>`\(\dfrac{23}{108}x=48-36\)
`=>`\(\dfrac{23}{108}x=12\)
`=>`\(x=\dfrac{1296}{23}\)
Vậy, `x = `\(\dfrac{1296}{23}\)
\(3^3.x^2-2^4.x^2=8^2.5-4^3.3^2\)
\(\Leftrightarrow x^2\left(27-16\right)=2^6.5-2^6.9\)
\(\Leftrightarrow11x^2=2^6.\left(5-9\right)=-4.2^6=-2^8\)
\(\Leftrightarrow x^2=-\dfrac{2^6}{11}< 0\)
\(\Rightarrow x\in\varnothing\)
\(\left[\left(\dfrac{1}{2}\right)^2-\left(\dfrac{1}{3}\right)^3\right]x+3^2.2^2=4^2.3\)
\(\Leftrightarrow\left(\dfrac{1}{4}-\dfrac{1}{27}\right)x+36=48\)
\(\Leftrightarrow\dfrac{23}{108}x=12\Leftrightarrow x=\dfrac{12.108}{23}=\dfrac{1296}{23}\)
a) 9 234 : [3 . 3. (1 + 83)] = 9 234 : [3 . 3 . (1 + 512)]
= 9 234 : [3 . 3 . 513] = 9 234 : 4617 = 2
b) 76 - {2 . [2 . 52 - (31 - 2 . 3)]} + 3 . 25
= 76 - {2 . [2 . 25 - (31 - 6)]} + 75
= 76 - {2 . [50 - 25]} + 75 = 76 - {2 . 25} + 75 = 76 - 50 + 75 = 101
A = \(\frac{3}{\left(1.2\right)^2}+\frac{5}{\left(2.3\right)^2}+...+\frac{101}{\left(50.51\right)^2}\)
= \(\frac{3}{1.4}+\frac{5}{4.9}+...+\frac{101}{2500.2601}\)
= \(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{9}+...+\frac{1}{2500}-\frac{1}{2601}\)
= \(1-\frac{1}{2601}=\frac{2600}{2601}\)
(19x + 2 . 52) : 14 = (13 - 8)2 - 42
(19x + 50) : 14 = (13 - 8)2 - 42 = 25 - 16 = 9
19x + 50 = 9 . 14 = 126
19x = 126 - 50 = 76
x = 76 : 19 = 4
Chúc bạn học tốt!!!!!
( 19x + 2.52 ) : 14 = ( 13 - 8 )2- 4 2
( 19x + 2.52 ) : 14 = 52- 4 2
( 19x + 2.52 ) : 14 = 25- 16
( 19x + 2.52 ) : 14 =9
( 19x + 50 ) : 14 =9
19x + 50=9 . 14
19x + 50=126
19x=126-50
19x=76
x=76:19
x=4
(19x + 2.5²) : 14 = (13 - 8)² - 4²
(19x + 2.25) : 14 = 5² - 16
(19x + 50) : 14 = 25 - 16
(19x + 50) : 14 = 9
19x + 50 = 9 . 14
19x + 50 = 126
19x = 126 - 50
19x = 76
x = 76 : 19
x = 4
\(\left(19x+2.5^2\right):14=\left(13-8\right)^2-4^2\)
\(\Rightarrow\left(19x+50\right):14=25-16\)
\(\Rightarrow19x+50=9.14=126\)
\(\Rightarrow19x=76\)
\(\Rightarrow x=76:19=4\)
\(\left(3x-2^2.3\right):8+2.5=13\)
\(\Leftrightarrow\left(3x-4.3\right):8+10=13\)
\(\Leftrightarrow\left(3x-12\right):8=13-10\)
\(\Leftrightarrow\left(3x-12\right):8=3\)
\(\Leftrightarrow3x-12=24\)
\(\Leftrightarrow3x=36\)
\(\Leftrightarrow x=12\)
Vậy ................